Outcome of biopsy‐proven lupus nephritis with low glomerular filtration rate at presentation. (17th July 2020) - Haridasan, Satish; Rathi, Manish; Sharma, Aman; Nada, Ritambhra; Kumar, Sachin; Ramachandran, Raja; Kohli, Harbir Singh
Abstract: Objectives: Currently, there is limited data regarding the outcomes of lupus nephritis (LN) with moderate to severe renal failure at presentation (defined by low glomerular filtration rate; GFR <30 mL/min). Methods: Sixty‐four patients with biopsy‐proven LN and estimated GFR (eGFR) <30 mL/min were prospectively analyzed. Outcome measure of persistently low eGFR, end‐stage renal disease (ESRD) or death at 365 days were grouped as Major Adverse Kidney Events (MAKE365). Results: Diagnosis of lupus was simultaneous with onset of renal disease in 60% of cases. Histologically, 82.3% (n = 51) were class IV, the median serum creatinine was 4 mg/dL (interquartile range [IQR] 3.1‐5.9 mg/dL), median eGFR was 13.75 mL/min (IQR 9.25‐19 mL/min) and 42.2% (n = 27) required dialysis at presentation. Induction regimens included National Institute of Health (68.2%), Eurolupus protocol (10.9%) and mycophenolate mofetil (8%). Over 365 days, 23 (37.5%) subjects died, while 41 (62.5%) survived. The majority of deaths were due to infection and sepsis (14/23). Among the survivors, 70.7% had good renal outcome, 12.1% had persistently low GFR (<30 mL/min), while 17% developed ESRD. In this group, treatment response rate was 84.6% (complete response 25.6%, partial response 59%). Those with a better renal function at presentation had a good treatment response (100% vs. 40%). Altogether, n = 35 (54.6%) were included in the MAKE365 category. Between the renal survival group (n = 29) versus the MAKE365 group (n = 35) there was no difference in clinical or histological parameters. Conclusion: The current treatment protocols had a good response rate in patients with LN even with severe kidney injury at presentation. However, the risk of serious infections and subsequent mortality was high.